Incorporation of 2, 6‐Connected Azulene Units into the Backbone of Conjugated Polymers: Towards High‐Performance Organic Optoelectronic Materials. Issue 5 (28th December 2017) - Xin, Hanshen; Ge, Congwu; Jiao, Xuechen; Yang, Xiaodi; Rundel, Kira; McNeill, Christopher R.; Gao, Xike
Abstract: Azulene is a promising candidate for constructing optoelectronic materials. An effective strategy is presented to obtain high‐performance conjugated polymers by incorporating 2, 6‐connected azulene units into the polymeric backbone, and two conjugated copolymers P(TBAzDI‐TPD) and P(TBAzDI‐TFB) were designed and synthesized based on this strategy. They are the first two examples for 2, 6‐connected azulene‐based conjugated polymers and exhibit unipolar n‐type transistor performance with an electron mobility of up to 0.42 cm 2  V −1  s −1, which is among the highest values for n‐type polymeric semiconductors in bottom‐gate top‐contact organic field‐effect transistors. Preliminary all‐polymer solar cell devices with P(TBAzDI‐TPD) as the electron acceptor and PTB7‐Th as the electron donor display a power conversion efficiency of 1.82 %. Abstract : An effective strategy for achieving high‐performance polymers in optoelectronic materials by incorporation of 2, 6‐connected azulene units into the polymeric backbone is presented. Two examples of 2, 6‐connected azulene‐based conjugated polymers were designed and synthesized, with an electron mobility of >0.4 cm 2  V −1  s −1 for BGTC OFETs and a power conversion efficiency of >1.8 % for all‐polymer solar cells.